(untitled) (Texas Journal of Medical Science, 2025)
The article discusses about how effect Anti ulcer for stomach and duodenal ulcer and the distribution areas of the plants hypericum, plantago , as well as the unsurpassed role of leaves in promoting human health, the chemical composition and biological significance of vitamins hypericum, plantago, as well as several recommendations for the treatment of stomach and duodenal ulcerin modern medicine and medicine. traditional medicine based on the compound leaves hypericum, plantago, as well as data on the mechanism of action on the stomach and duodenal wall and their discussion.